Evolution of Jorm's concept of mental health literacy; implications for well-being - Martí-García, Celia (My University, 2023)
Mental health problems are a reality that, according to the WHO, affect more than 450 million people in the world. These disorders have a very high cost, both in terms of social and health care, leading to a poorer quality of life, family costs and discrimination from the rest of society, as a result of the stigma attached to mental health problems. Despite this facts, and the relationship found between well-being and help-seeking, many of those affected do not seek help, partly in an attempt to avoid what the label of being mentally ill carries with it. One of the factors identified for seeking care in cases where the individual's MH is altered, and which is related to stigmatising attitudes, is mental health literacy (MHL), understood as knowledge that helps to recognise, manage and prevent MHPs while reducing stigma. The term MHL was first formally coined in 1997 by Jorm et al. as the set of "knowledge and beliefs about MHPs that aid in their recognition, management or prevention". The authors concluded that MHL includes 3 types of connected concepts: knowledge, attitudes and help-seeking efficacy. However, there is still no consensus on the subject and, as a result, its measurement has been carried out in a rather heterogeneous manner, giving rise to some methodological problems when comparing data. It is from here that the following questions arise: What is MHL? What kinds of issues does the concept encompass in order to establish whether or not a person is MHL literate? What kinds of factors has MHL literacy competence been commonly related to? Although most studies start from Jorm's conception of mental health literacy, when analysing this concept we find different nuances, which need to be taken into account when carrying out future research, especially when developing new instruments for its measurement or implementing educational programmes.
Keywords: Salud mental -- Aspectos sociales; Enfermedades mentales -- Aspectos sociales; Mental health; Literacy; Well-being; Stigma